THE ACHIEVABILITY OF TARGET CONVECTION VOLUMES IN ON-LINE HEMODIAFILTRATION - A. B. Sabodash; G. A. Zemchenkov; N. S. Kazantseva; K. A. Salikhova; O. V. Makarova; Y. Y. Proletov; A. Y. Zemchenkov (Вестник трансплантологии и искусственных органов)
Aim. To evaluate the achievability of recommended convection volumes in hemodiafiltration (HDF) and impeding factors. Materials and methods. In short interventional one-center study among 67 stable prevalent dialysis patients we succeeded in achieving convection volume of more than 24 l/session in 60 patients (90%). Results. Substitution volume rose in the whole group from 21.1 ± 1.6 to 23.8 ± 1.2 l/session (p < 0.01). 12 patients, who didn`t achieve target volume had similar age, duration of renal replacement therapy and ultrafiltration rate as those who did. They differed from 55 patients who achieved target volume by substitution volume at first session in evaluation period (22.2 ± 1.7 vs. 23.6 ± 1.5 liters, р = 0.004), by transmembrane pressure (170 ± 40 vs. 146 ± 24 mmHg, р = 0.009) and by session duration (248 ± 15 vs. 262 ± 17 min, р = 0.0017). Blood flow rate also differed at the start of the study between the achievers and non-achievers: 353 ± 21 vs. 339 ± 19 ml/min, р = 0.035. The pressure in venous segment was lower in the achievers (154 ± 25 vs. 176 ± 36, р = 0.02) as well as transmembrane pressure (144 ± 24 vs. 164 ± 36, р = 0.014) which has been rising session by session in nonachievers. In non-achievers the membrane surface area was lower: 1.75 ± 0.2 vs. 1.91 ± 0.2 m2 (p = 0.02). In the multiple binary logistic regression model the session duration and membrane surface area were positive factors while the transmembrane pressure was negative one. Session prolonged by 15 min was associated with increase in relative chance to achieve target volume by 39% (95% CI 5–82%; р = 0.02). The membrane surface area enlarged by 0.1 m2 was linked with increase of chance by 4.2% (95% CI 0.2–8.4%; р = 0.04). The transmembrane pressure increased by 10 mmHg was associated with decreased chance to achieve target volume by 17% (95% CI 0–70%; р = 0.05). Conclusion. To achieve convection volume of 24 l/session one needs to afford effective blood flow rate, to increase the session duration and membrane surface area, avoiding high transmembrane pressure; severe comorbidity can hamper achieving target volume. Accumulating data of different studies are rather divergent in conclusions with regard to required target volume and ways to ensure its achievability, so study continuation is mandatory.